Emerging Traditions : Toward a Postcolonial Stylistics of Black South African Fiction in English. - Briault Manus, Vicki (Lexington Books, 2012)
The book, an academic monograph, is a comprehensive study of the socio-linguistics of black South African literature in English from its beginnings, grounded in historical and political change as befits a postcolonial approach, with the inherent struggles between language and power. Its innovation is that it traces stylistic devices used by successive generations of black writers back to such sources as African orature, Indigenous cultures and languages, and Indigenization and creolization of South African languages.